Optimal timing and technique for endoscopic management of dysphagia in pediatric aerodigestive patients. (November 2021) - Wineski, R.E.; Panico, E.; Karas, A.; Rosen, P.; Van Diver, B.; Norwood, T.G.; Grayson, J.W.; Beltran-Ale, G.; Dimmitt, R.; Kassel, R.; Rogers, A.; Leonard, M.; et al.
Abstract: Introduction: The best strategy to manage an interarytenoid defect [Type 1 laryngeal cleft (LC-1) or deep interarytenoid groove (DIG)] in pediatric aerodigestive patients with dysphagia remains uncertain. This study compared benefit of interarytenoid augmentation (IAA) to suture repair or clinical observation alone in pediatric patients. Methods: A 3-year retrospective, single-center analysis of children with dysphagia undergoing endoscopic airway evaluation was performed. Physician preference guided treatment plan: suture repair with CO2 laser, IAA (carboxy methylcellulose or calcium hydroxyapatite), or observation. Primary outcome was improved post-operative diet. Significance was assumed at p < 0.05. Results: 449 patients underwent diagnostic endoscopy. Mean age (±SD) at procedure was 21 ± 13 months, with nearly one fourth (28 %) of children ≤ 12 months. Eighty (18 %) had either an LC-1 (n = 55) or DIG (n = 25). Of these, 35 (42 %) underwent suture repair, 22 (28 %) IAA, and 23 (30 %) observation only. Aspiration improved overall in the interventional groups compared to observational controls (58 % vs. 9 %, p < 0.05), with no change in benefit observed by age of intervention. IAA was as effective as suture repair (59 % vs 55 %, p = 0.46). In patients with only a DIG, IAA intervention alone significantly improved swallow function (66.6 % vs. 0 %, p < 0.05). Conclusion: In pediatric aerodigestive patients with dysphagia, 18 % of children have an addressable lesion. IAA or suture repair similarly improves dietary advancement. IAA improves swallow function in patients with DIG. These findings support a novel protocol to intervene in dysphagia patients with LC-1 or DIG via IAA at the initial operative evaluation.